Evaluating the efficacy of the education and training program of the TCPS 2. (July 2017) - Stockley, Denise; Kinderman, Laura; Egan, Rylan; Lam, Chi Yan; Hastings, Amber
In 2011, the Secretariat on Responsible Conduct of Research launched a set of educational opportunities to facilitate and enhance the dissemination of TCPS 2, the 2nd edition of the Tri-Council Policy Statement: Ethical Conduct for Research Involving Humans (2010), which guides Canadian research ethics. Three educational modalities were implemented to aid participants in developing or refining their ethical understanding and practice: (i) Regional Workshops, which brought together diverse disciplinary perspectives; (ii) the CORE tutorial, which enabled individuals to discover the various aspects and applications of the Policy; and (iii) Webinars, which provided participants with the opportunity to explore deeper dimensions of research ethics. This article reports on the findings of a national program evaluation team which measured the effectiveness of the educational program and provided recommendations for future opportunities.